South by Java Head - MacLean, Alistair, 1922-1987. (New York : American Reprint Co., 1975)
A combination of soldiers, nurses, civilian refugees, a young boy, and a spy attempt to escape the burning city of Singapore aboard the "Kerry Dancer," a freighter staffed by an infamous captain and crew, the "Viroma," which is sunk, and eventually in open boats as they are chased across the South China Sea.
Reprint of the 1958 ed. published by Fawcett Publications, Greenwich, Conn.
Adult
Keywords: World War, 1939-1945 -- Fiction; World War, 1939-1945 -- Fiction